The Vocational High School Student’s Computational Thinking Skills Comparison between Online and Offline Instructional Process in The Computer Network Subject Context - Herlambang, Admaja Dwi; Nugraha Kresna Mukti; Satrio Hadi Wijoyo (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
This study aims to see how high the difference in the average score of computational thinking skills is owned by students who carry out online learning with students who carry out offline learning and how high the significance level of the difference in the average score is. The approach used in this study uses assessment tools to measure the scores of students’ computational thinking skills. Sampling was done using a non-probability sampling technique for the 12th-grade students in computer network subjects of vocational high school. The mechanism used in this study was to provide research questions to each respondent under the learning mechanism, each of which consisted of 15 students. Based on the results of statistical calculations, it was found that the average/mean of the online mechanism group was 13.27, and the offline group was 17.73. In the Mann-Whitney U test, a score of 0.159 was also obtained. Comparison of the Mann-Whitney U test results with the test rules of 0.159 > 0.05. The conclusion is that there is a difference between the scores of the computational thinking skills of students who carry out online and offline learning, but this difference is not significant.